Khyber Pakhtunkhwa Food Outlook Report (Rabi) 2022 - Rabi crops 2021-22 - Raja, Sehrish; Tauqir, Aisha; Qureshi, Tehseen Ahmed; Rana, Abdul Wajid (International Food Policy Research Institute, 2022)
A Food Outlook report explains the crop situation with in specific geographical boundaries. It identifies the past trends in area, production, yield, and price and predict future trends based on past values, thereby helping the government entities to make well informed decisions and farm growers to maximize profitability. The purpose of Khyber Pakhtunkhwa Food Outlook Report is to understand the trends and forecasts relating to area, production, yield, and price of four major rabi crops of KP i.e., wheat, gram, garlic, and onion for 2021-22 cropping season. The report provides commodity balance sheet showing changes in crop stocks, utilization, and output. Moreover, the forecasts analysis may help in anticipating any upcoming shock related to food demand and supply. It also helps farmers to take advantage of emerging opportunities and prevent themselves from any anticipated losses.